REHABILITATION / MODERNIZATION WORKS RELATED TO M4b DEPOSIT COAL REMOVAL MACHINES - Alin STĂNCIOIU (Fiabilitate şi Durabilitate)
The paper presents the study for the rehabilitation / modernization works related to the coal removal machine from the M4b depot being destined to unload the solid fuel depots, the technological role being to take the solid fuel from the stacks and to deposit it on a belt conveyor.